The revolt of the poem - Flores, Guilherme Gontijo (2019)
In this essay I shall analyse some discussions of Furio Jesi, Hannah Arendt and other authors on the relations between revolt and revolution, besides Walter Benjamin’s essay on The Destructive Character and excerpts from Paulo Ferraz, Alejandra Pizarnik, Paul Celan and Guimarães Rosa, in order to propose ways to understand the poem’s power of revolt beyond an explicit political engagement.